The biochemistry of feed efficiency, energy metabolism, and mitochondrial function, an animal and molecular approach - Baldassini, Welder Angelo (2017)
Energetic efficiency is important for health (e.g. genesis of obesity in humans), socio-economically important for meat production systems (e.g. feed cost to produce high quality protein) and important for the environment (e.g. use of natural resources and production of green house gases for meat production). Mitochondria are organelles that play an essential role in cellular metabolism and homeostasis related to energy utilization. These processes involve several proteins to ensure continuous availability of energy to the cells. The Shc proteins play a key role in substrate oxidation and energy metabolism. Additionally, the mitochondrial uncoupling proteins (UCPs) participate in physiological processes that may account for variation in energy expenditures in tissues. However, the mechanisms behind energy expenditure in animals are largely unknown. Thus, in order to study the energy metabolism and mitochondria function, studies using a nutritional, biochemical and molecular approaches were conducted with mice and cattle. The purpose of the first study was to determine if Shc proteins influence the metabolic response to acute (5-7 days) feeding of a high fat diet (HFD). To this end, whole animal energy expenditure and substrate oxidation were measured in the Shc knockout (ShcKO) and wild-type (WT) male mice consuming either a control or HFD diet. The activities of enzymes of glycolysis, the citric acid cycle, electron transport chain (ETC), and β-oxidation were investigated in liver and skeletal muscle. The study showed that ShcKO increases (P < 0.05) energy expenditure (EE) adjusted for either total body weight or lean mass. This change in EE could explain the decrease in weight gain observed in ShcKO versus WT mice fed an HFD. Thus, our results indicate that Shc proteins should be considered as potential targets for developing interventions to mitigate weight gain on HFD by stimulating EE. Although decreased levels of Shc proteins influenced the activity of some enzymes in response to high fat feeding, such as increasing the activity of acyl-CoA dehydrogenase, it did not produce concerted changes in enzymes of glycolysis, citric acid cycle or the ETC. However, the physiological significance of these changes in enzyme activities remains to be determined. The purpose of experiment 2 was to study the association among heat production, blood parameters and mitochondrial DNA (mtDNA) copy number in Nellore bulls with high and low residual feed intake (RFI). The RFI values were obtained by regression of dry mater intake (DMI) in relation to average daily gain and mid-test metabolic body weight. Thus, 18 animals (9 in each group) were individually fed in a feedlot for 98 days. The heart rate (HR) of bulls was monitored for 4 consecutive days and used to calculate the estimated heat production (EHP). Electrodes were fitted to bulls with stretch belts and oxygen consumption was obtained using a facemask connected to the gas analyzer and HR was simultaneously measured for 15 minutes period. Daily EHP was calculated multiplying oxygen pulse (O2P) by the average HR, assuming 4.89 kcal/L of O2. Blood parameters such as hematocrit, hemoglobin, and glucose were assayed between 45 and 90 days. Immediately after slaughter, liver, muscle and adipose tissues (subcutaneous and visceral fat) were collected and, subsequently, mtDNA copy number per cell was quantified in tissues by quantitative real-time PCR. The proteome of hepatic tissue and levels of mitochondrial UCPs were also investigated. We found similar EHP and O2 consumption between RFI groups, while low RFI bulls (more efficient in feed conversion) shown lower HR, hemoglobin and hematocrit percentage (P < 0.05), confirming previous data from our group. In addition, 71 protein spots in liver were differentially expressed (P < 0.05) and no differences were detected for UCPs levels between RFI groups. Finally, there was no association between amounts of mtDNA and the RFI phenotypes, suggesting that mitochondrial abundance in liver, muscle, and adipose tissue was similar between efficient and inefficient groups. However, additional studies to confirm this hypothesis are needed.